Parenteral organophosphorus poisoning in a rural emergency department: a case report - Malla, Gyanendra (BioMed Central, 2013)
BACKGROUND: Poisoning is a common presentation in the emergency department. Oral exposures to organophosphorus compounds are especially frequent in rural and agricultural regions of South Asia and throughout the developing world. CASE PRESENTATION: Here we report a case of deliberate self-harm with an organophosphorus pesticide via the relatively uncommon parenteral route. A young woman injected herself with chlorpyriphos. Although the cholinergic effects were mild, cellulitis and abscess development were noted as a result. CONCLUSION: Resource limited agricultural countries like Nepal present health care workers with numerous challenges in poisoning management. This case represents a rare but potentially morbid method of agrochemical poison exposure.